Activation of GPR40 Suppresses AGE-Induced Reduction of Type II Collagen and Aggrecan in Human SW1353 Chondrocytes - Gu J; Lin H; Zhang Y; Xu T; Wang T; Xue X; Zhang W; Liu H (Dove Medical Press, 2020)
Jiaxiang Gu,1,* Hongsheng Lin,2,* Yiyuan Zhang,1 Tao Xu,1 Tianliang Wang,1 Xiawei Xue,1 Wenzhong Zhang,1 Hongjun Liu1 1Department of Orthopaedics, Subei People’s Hospital Affiliated to Yangzhou University, Yangzhou 225000, People’s Republic of China; 2Department of Orthopaedics, Xiangya Second Affiliated Hospital of Center South University, Changsha 410008, People’s Republic of China*These authors contributed equally to this workCorrespondence: Hongjun Liu; Wenzhong ZhangDepartment of Orthopaedics, Subei People’s Hospital Affiliated to Yangzhou University, No. 98 of West Nantong Road, Yangzhou 225000, Jiangsu, People’s Republic of ChinaTel/Fax +86 514-87373012Email hongjunl282@yeah.net; zhixianyongo@163.comIntroduction: Osteoarthritis (OA) is an age-related chronic degenerative disease. Accumulation of advanced glycation end products (AGEs) induces degradation of the articular extracellular matrix (ECM) and is considered a critical step toward the development and progression of OA. GPR40 is a well-known free fatty acid receptor, which possesses pleiotropic effects in different types of diseases. However, the biological function of GPR40 in OA is indistinct. The purpose of the present study was to determine the impact of the GPR40 agonist GW9508 on AGEs-treated chondrocytes.Materials and Methods: Cultures of human SW1353 chondrocytes were stimulated with GW9508, followed by exposure to 100 μg/mL AGEs. Gene and protein expression of TNF-α, IL-6, MMP-3, MMP-13, ADAMTS-4, and ADAMTS-5 were measured by real-time PCR and ELISA analysis. The levels of type II collagen, aggrecan, and nuclear NF-κB p65 were measured by Western blot analysis. A luciferase assay measured the transcriptional activity of NF-κB.Results: The results show that treatment with AGEs decreased the expression of GPR40 in human SW1353 chondrocytes. Treatment with GW9508 plays a beneficial role in protecting type II Collagen and aggrecan from degeneration by attenuating the expression of MMP-3, MMP-13, ADAMTS-4, and ADAMTS-5. Additionally, GW9508 reduces the appearance of pro-inflammatory cytokines and suppresses NF-κB activation in AGEs-induced chondrocytes. Notably, co-treatment with GW1100, a specific antagonist of GPR40, abolishes the beneficial role of GW9508 against AGEs, implying that GPR40 mediates these effects of GW9508.Conclusion: Our results suggest that GPR40 is a novel therapeutic target for OA and that GPR40 agonists, including GW9508, may have therapeutic potential in preventing and slowing the progression of OA.Keywords: osteoarthritis, GPR40, GW9508, MMPs, ADAMTS, NF-κB